Coping Strategies and Perceived Support of Student-Mothers at The University of Education, Winneba-Campus - Anane, Cecilia; Adangabe, Amos Amuribadek; Inkoom, Daniel (South Asian Journal of Social Sciences and Humanities, 2021)
This research work explored the perceived support (needs) of student-mothers as they undertake motherhood and studentship concurrently at the University of Education, Winneba campus of Ghana. The study is a qualitative piece that employed the case study design. Twenty student-mothers between the ages 26 – 40 with at least a child aged five years or below staying with them full time on campus were interviewed. The student-mothers were selected through purposive and snowball sampling techniques. An unstructured interview was employed by the researchers to gather data for the research. It emerged from the study that mothering had effects on the health, social, and academic life of student-mothers. The data further revealed that student-mothers coped with their economic challenges by reducing their expenses and budgeting. The study went on to reveal that student-mothers want their lecturers to be more understanding and flexible to reschedule their lecture periods.
Keywords: Coping Strategy; Student-mothers